Sustainability Strategy of PT XYZ in Entering the Blue Ammonia Industry in Indonesia - Zulmi, Muhammad Indra; Zulbainarni, Nimmi; Sartono, Bagus (Journal of International Accounting, Taxation and Information Systems, 2025)
Blue ammonia is emerging as a critical transitional solution in the global energy transition, with market volumes projected to grow from 1.1 million tons in 2023 to 9.2 million tons by 2028, and Indonesia has positioned it as a key pillar of its net-zero strategy by 2060. This article analyses the sustainability strategy of PT XYZ, an Indonesian integrated energy and chemical company, in entering the blue ammonia industry. Produced from natural gas with carbon capture and storage (CCS), blue ammonia offers a decarbonisation pathway for hard-to-abate sectors. PT XYZ is converting an existing ammonia plant but faces challenges including CCS costs, gas-price volatility, financing needs, and stringent international standards. The study aims to (1) map external opportunities and threats, (2) assess PT XYZ's internal resources and capabilities, and (3) formulate sustainability-oriented strategic alternatives. A mixed-method approach combines PESTLE and Porter's Five Forces analyses with Resource-Based View and VRIO assessment, followed by SWOT and TOWS synthesis using document review, interviews, focus groups, and expert questionnaires. Findings shed light that PT XYZ operates in a supportive yet demanding environment, possessing strengths in HSE culture, gas procurement, CCS design, MRV readiness, and contract management, alongside gaps in equity gas, CCS agreements, blended finance, and anchor contracts. The resulting SO, WO, ST, and WT strategies provide a roadmap for de-risking investment, securing premium markets, and aligning with long-term decarbonisation goals.